(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
Inés Suárez was the first Spanish woman to come to the territory later known as Chile. This paper examines her role in the conquista as presented in the documents of the period, as well as in historical and historico-fictional accounts produced this century in Chile and abroad. It concludes that the image of her as a brave, intelligent, and saintly woman, a cross between Florence Nightingale and Joan of Arc, is firmly rooted in reality.